The Suicidal Self in Cyberspace: Discursive Constructions of Identity in a Pro-Recovery Suicide Forum - Alvarez, Mike (Frontiers in Communication, 2021)
The proliferation of suicide-related content online has led to widespread fears that suicidal persons are at elevated risk in our networked society. Though much research has been done on the benefits and harms of digital technologies, few studies have attended to the deep discursive meanings co-created by suicidal users. The present study attends to meanings about identity interactionally created by members of SuicideForum.com (SF), a pro-recovery website. Methodologically, I collected a purposive sample of 2119 posts across 131 threads, which I then examined using cultural discourse analysis, tracking discursive hubs like "suicide" and "suicidal" to arrive at corresponding radiants of meaning. Findings reveal two sets of discursive themes: one speaks to problematic identities, the other to a self emancipated from suicidality. The suicidal self is expressed in discourse as the product of a fractured identity, marked by schism between an authentic "inner self" and a socially aligned but inauthentic "outer self." However, resolution of fractured identities depends not on harmonious fusion but on reconciliation. Moreover, staying alive - continuing to be - is contingent upon recognizing that every life, including one's own, has value, finding purpose and meaning, and tending to others' well-being. The analysis uncovers discrepancies between SF users' folk understanding of the suicidal self and that espoused by dominant (i.e. biopsychiatric) models. Their implications for clinical and therapeutic practice are discussed.